Recent Changes of Some Observed Climate Extreme Events in Kano. (2nd February 2015) - Gbode, Imole Ezekiel; Akinsanola, Akintomide Afolayan; Ajayi, Vincent Olanrewaju
Abstract : Observed rainfall and temperature data for the period 1960–2007 were used to examine recent changes of extreme climate over Kano, located in the Sahelian region of Nigeria. The RClimDex software package was employed to generate nine important climate indices as defined by the Expert Team on Climate Change Detection, Monitoring and Indices (ETCCDMI). For the entire period, the results show a warming trend, an increased number of cool nights, more warm days, and a strong increase in the number of warm spells. The rainfall indices show a slight increase in annual total rainfall, a decrease in the maximum number of consecutive wet days, and a significant increase in the number of extremely wet days. Such changes in climate may result in an increasing demand for domestic energy for cooling and a higher evaporation rate from water bodies and irrigated crop. These findings may give some guidance to politicians and planners in how to best cope with these extreme weather and climate events.